Racialised politics of (in)security and the COVID-19 Westfailure. Issue 1 (2nd January 2021) - Pan, Chengxin
ABSTRACT: Many Western countries, the perceived 'zone of security' in world politics, have failed miserably in their COVID-19 responses. This 'COVID-19 Westfailure', this piece argues, has in large part to do, rather ironically, with the very Western knowledge and practice of dividing the world into zones of security and insecurity along some (often imagined) global colour lines. The racialised politics of (in)security contributes to the COVID-19 Westfailure on three levels. On the ontological level, it mistakes racialised Others for the source of a fundamentally non-racial and transnational threat. Methodologically, its adoption of often racist half-measures has proven largely ineffective. Epistemologically, epistemic racism fails to learn valuable lessons and experiences from its Others who are routinely viewed as civilisationally and scientifically inferior and backward. The pandemic, neither recognising nor operating along colour lines, has laid bare the limits and fallacies of Western racialised knowledge and practice of security.